Origin of Al-rich chondrules in CV chondrites: Incorporation of diverse refractory components into the ferromagnesian chondrule-forming region. (1st March 2020) - Zhang, Mingming; Lin, Yangting; Tang, Guoqiang; Liu, Yu; Leya, Ingo
Abstract: Aluminum-rich (Al2 O3 > 10 wt%) chondrules (ARCs) are important chondritic components that petrologically link two other major chondritic components, ferromagnesian chondrules (FMCs) and calcium-aluminum-rich inclusions (CAIs), which formed in different regions of the protoplanetary disk. They are closely related to FMCs as indicated by their similar igneous textures, mineral assemblages, and Al-Mg isotope systematics; meanwhile, they have genetic a relationship with CAIs as indicated by their distinctly Al2 O3 -rich compositions and occasional occurrences of relict CAI minerals. In order to further understand their formation mechanism and genetic relationships to FMCs and CAIs, nine ARCs and three ARC-related objects from Allende (CV3 oxidized), Leoville (CV3 reduced), and the ungrouped Ningqiang carbonaceous chondrites were studied for petrology, mineralogy, bulk compositions, rare earth element (REE) abundances, and in situ oxygen isotopic compositions. Our results suggest that (i) ARCs crystallized from incompletely molten droplets with crystallization sequences mainly determined based on their bulk compositions. Projection of their bulk compositions onto the forsterite-saturated tridymite-diopside-spinel diagram allows us to classify them into Al-rich [Sp], Al-rich [En], and Al-rich [Plag]; (ii) ARC precursors are mixtures of refractory materials and the precursors of FMCs, in which the refractory materials have diverse sources rather than a single type of CAI/AOA (amoeboid olivine aggregate); this is inferred from the bulk compositions, relict minerals (both coarse- and fine-grained spinel, olivine, and Al-Ti-diopside), and various CAI-like REE patterns (unfractionated Group I/III and highly fractionated Group II/II-like) of ARCs. The sources include AOAs and igneous Type B/C CAIs; (iii) ARCs were melted in the FMC-forming region, possibly by the same heating mechanism or during the same transient heating event, which is consistent with the similar oxygen isotopic compositions of their phenocrysts (Δ 17 O = −5.2 ± 1.7‰, 2SD). Thus, we consider that ARCs formed by melting of mixtures of diverse refractory components with the FMC precursors in the FMC-forming region.